The Effect of Indosat Ooredo Mini Outlet Customer Service Quality on Indosat Ooredo Customer Satisfaction in Karangasem Regency - Ni Komang Dwi Arisandi; Pebriansyah, Pebriansyah (Jurnal Multidisiplin Sahombu, 2025)
The Indonesian telecommunications sector is highly competitive and one of the fastest growing industries. Mobile operators have shifted from competing on rates or network coverage to focusing on service quality. A company's ability to provide superior and satisfying services is key to business sustainability and customer loyalty. Quantitative methods were used in this study to test and analyze the effect of the service quality of Indosat Ooredoo Mini Outlets on the satisfaction of Indosat Ooredoo customers in Karangasem Regency. Using five dimensions, variable X measures service quality: tangibles, reliability, responsiveness, assurance, and empathy. On the other hand, variable Y, or customer satisfaction, is measured through metrics such as conformity with expectations, interest in repurchasing, and recommendations from others. In this study, all Indosat Ooredoo customers in Karangasem Regency who had used the Customer Service at Mini Gerai were the subjects. The purposive sampling method was used to collect samples, and the total number of respondents who filled out the questionnaire was thirty. Multiple linear regression analysis was used to examine the data to validate the hypothesis and determine how significant the influence of the independent variables was on the dependent variable. Quantitative research results show that the quality of Indosat Ooredoo Mini Outlet Customer Service, which consists of tangibles, reliability, response, assurance, and empathy elements, greatly affects Indosat Ooredoo customer satisfaction in Karangasem Regency. The results show that maintaining and improving service quality in all aspects is very important to increase customer loyalty and satisfaction in the Karangasem Regency area.